1996
DOI: 10.1137/s0363012994263469
|View full text |Cite
|
Sign up to set email alerts
|

On Finite-Gain Stabilizability of Linear Systems Subject to Input Saturation

Abstract: This paper deals with (global) finite-gain input/output stabilization of linear systems with saturated controls. For neutrally stable systems, it is shown that the linear feedback law suggested by the passivity approach indeed provides stability, with respect to every L p-norm. Explicit bounds on closed-loop gains are obtained, and they are related to the norms for the respective systems without saturation. These results do not extend to the class of systems for which the state matrix has eigenvalues on the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
137
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(138 citation statements)
references
References 20 publications
0
137
0
1
Order By: Relevance
“…Results which are (vaguely) related to Proposition 3.4 can be found in [20], where it is shown that, under suitable assumptions, a "small" signal ISS property holds for Lur'e systems with nonlinearities of "saturation" type.…”
Section: ) Does Not Hold) (B) Under the Additional Assumption That mentioning
confidence: 99%
See 1 more Smart Citation
“…Results which are (vaguely) related to Proposition 3.4 can be found in [20], where it is shown that, under suitable assumptions, a "small" signal ISS property holds for Lur'e systems with nonlinearities of "saturation" type.…”
Section: ) Does Not Hold) (B) Under the Additional Assumption That mentioning
confidence: 99%
“…Moreover, a further corollary (Corollary 3.11) shows that the conditions of the usual textbook version of the circle criterion for global asymptotic stability (see [7,16,27]) are actually sufficient for ISS. Finally, we mention that if A is not Hurwitz and f is bounded (for example, if f is of "saturation" type), then the nonlinearity is not "powerful" enough to counteract large (but bounded) inputs (at least if im B ⊂ im B e ) and the Lur'e system (1.1) is not ISS (see [20] and Proposition 3.4 in the current paper). Correspondingly, it is not difficult to show that if A is not Hurwitz, f is bounded and every complex output feedback gain in the ball {F : F − K < r } is stabilizing, then there does not exist α ∈ K ∞ such that (1.2) holds (see Proposition 3.4).…”
Section: Introductionmentioning
confidence: 99%
“…The same discussion holds replacing V λ with W λ satisfying (18). Reshaping V 0 via the flow of a vector field G has the interesting advantage that it replaces the above difficult condition on V λ given by equation (20) by a simpler condition on G as shown by the following lemma: Lemma 4.1.…”
Section: Reshaping Lyapunov Functions Via the Flow Of A Vector Fieldmentioning
confidence: 91%
“…In [18] (proof of Lem. 2), the case where f 0 is a linear vector field and where the control vector fields depends on the control (systems are non affine in the control but it has a particular structure) is studied.…”
Section: Assumption 31 (Jurdjevic-quinn Conditions)mentioning
confidence: 99%
See 1 more Smart Citation